FLOATING TEACHING LABORATORY: PRACTICE AS A TEACHING QUALIFICATION: Laboratório de Ensino Flutuante: a prática como uma qualificação de ensino - Calazans, Danilo (Arquivos de Ciências do Mar, 2022)
The importance of the ocean as an economic source for humanity has been standing out for decades. Ocean study is an example of multi- and interdisciplinary science that includes studies on physical, chemical, and geological variables such as ocean currents, temperature, light, salinity, dissolved nutrients, organic and inorganic particles, and studies of organisms that inhabit from its surface to the deep sea. The data used in oceanographic studies are obtained through various instruments and collection techniques. This multidisciplinarity results in the need to use a vessel as a laboratory where it is possible to integrate all these components. Keywords: marine science, vessel, training, instruments, data.